The Cancer Centre That Never Was: The Organisation of Danish Cancer Research 1949-1992 - Marie Louise Conradsen (Copenhagen Business School (CBS), 2014)
The Cancer Centre That Never Was - The organisation of Danish cancer research 1949-1992 This thesis analyses the demise of a remarkably resilient idea relating to the establishment of a public-private comprehensive cancer centre in Denmark. Plans to establish the cancer centre were made for more than four decades without ever amounting to an actual centre establishment. After 43 years, the cancer research community finally deemed the idea fruitless and no further plans were made. But why did it take so long to abandon an idea that had at no point in its existence proved its worth or rationale? And why were better alternatives not explored although they presented themselves along the way? This thesis employs a theoretical framework inspired by economist Douglass C. North and sociologist Pierre Bourdieu to answer these questions and determine whether or not the history of the cancer centre that never was can be seen as a case of path dependence. In doing so, the thesis focuses on three main questions: 1) Why was the goal of building a public-private comprehensive cancer centre never reached? 2) Why did 43 years pass before the idea of the centre was abandoned? 3) And is it possible to answer these questions by merely seeing the matter as a succession of historical events, or should it be seen in the perspective of path dependence? By using North's concepts of formal and informal institutions, the thesis shows that the failure to establish a centre is closely linked to unfavourable institutional matrices at different times in history. The thesis also shows how the idea of the centre was promoted for different reasons by various groups of actors in the case-story, and that the idea was most vigorously promoted in times of economic recession as a tool to secure either better funding for individual cancer research groups or for the anti-cancer cause in general. At every point in history, at least one group of involved actors did not have their needs met by the institutional matrix and used the idea of a cancer centre as a way of expanding the matrix to their own advantage – thereby prolonging the lifespan of the idea. The history of the Cancer Centre That Never Was may, on the surface, seem irrational because it never paid off in the form of an actual cancer centre. However, by employing the concepts of North (institutions, path dependence) and Bourdieu's theory on social fields and actor behavior it seems that the path paid off in different ways and on different levels than through the establishment of an actual centre. The involved public and private actors in the cancer research community had other reasons for supporting a cancer centre than what was formally presented as the primary objective: the scientific coordination of cancer research in Copenhagen. Reasons that reflected a power struggle between individual researchers, public and private research organisations and the Danish Government on issues relating to the financing Danish cancer research. The thesis concludes that path dependence did most likely occur in the story of the Cancer Centre That Never Was.
hdl:10398/9025
Keywords: 650